DISASTER RISK REDUCTION LESSON FROM HALMAHERA SWARM 2017 AND LOMBOK EARTHQUAKE 2018 - Rohmat Hidayat; Admiral Musa Julius; Wilopo Wilopo; I Dewa Ketut Kerta Widana (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2020)
Three years ago, we were shocked by Halmahera Swarm 2017 and two years ago Lombok Earthquake 2018. This article is purpose to show the swarm earthquake which occur fluently in Indonesia, such as Halmahera Swarm 2017 and Lombok Earthquake 2018, also the lesson for Disaster Risk Reduction. The lesson learnt from those earthquakes is importance of the follow up in the form of capacity building in communities on responding the earthquake hazard.